Genetic diversity and population structure analysis of European hexaploid bread wheat (Triticum aestivum L.) varieties. - Nanna Hellum Nielsen; Gunter Backes; Jens Stougaard; Stig Uggerhøj Andersen; Ahmed Jahoor (PLoS ONE)
Progress in plant breeding is facilitated by accurate information about genetic structure and diversity. Here, Diversity Array Technology (DArT) was used to characterize a population of 94 bread wheat (Triticum aestivum L.) varieties of mainly European origin. In total, 1,849 of 7,000 tested markers were polymorphic and could be used for population structure analysis. Two major subgroups of wheat varieties, GrI and GrII, were identified using the program STRUCTURE, and confirmed by principal component analysis (PCA). These subgroups were largely separated according to origin; GrI comprised varieties from Southern and Eastern Europe, whereas GrII contained mostly modern varieties from Western and Northern Europe. A large proportion of the markers contributing most to the genetic separation of the subgroups were located on chromosome 2D near the Reduced height 8 (Rht8) locus, and PCR-based genotyping suggested that breeding for the Rht8 allele had a major impact on subgroup separation. Consistently, analysis of linkage disequilibrium (LD) suggested that different selective pressures had acted on chromosome 2D in the two subgroups. Our data provides an overview of the allele composition of bread wheat varieties anchored to DArT markers, which will facilitate targeted combination of alleles following DArT-based QTL studies. In addition, the genetic diversity and distance data combined with specific Rht8 genotypes can now be used by breeders to guide selection of crossing parents.